PERKEMBANGAN UMKM (USAHA MIKRO KECIL DAN MENENGAH) DI INDONESIA - Yuli Rahmini Suci (Fakultas Ekonomi Universitas Pasir Pengaraian, 2017)
This research deals with the development of the growth of SMEs in Indonesia. Some literature referred to troubleshoot problems that occur and the use of secondary data obtained from relevant agencies such as: CPM, BI and Ministry of Cooperatives and SMEs. Weakness faced by SMEs in enhancing the ability of business is extremely complex and covers a wide range of indicators which one with the other inter-related, among others; lack both the amount and source of capital, lack of managerial ability and the skills to operate in organizing and limited marketing. Besides, things are also unhealthy competition and economic pressures that lead to the business scope becomes narrow and limited. This concern is based on that Indonesia will face the MEA and the free market. Ketiaka it accomplished its demands are SMEs should be able to compete. However, all the problems can be resolved with some policies that open opportunities for SMEs to have access to the banking industry dengna easy. Because the growth of loans disbursed only 13.6% of the banking sector. It addressed the problems originating from the capital can be easily resolved and affected the management and the resulting product will be more competitive. Challenges MEA is feared by the Government can be dealt with better.